Intermediate microeconomics : - Varian, Hal R. (W.W. Norton & Co., 2006)
Professor Varian’s lucid prose guides students through the fundamentals of microeconomic analysis while emphasizing real-world economic problems and incorporating coverage of the most innovative subjects in the discipline. The Seventh Edition has been carefully updated and revised, adding a wealth of new applications and examples that analyze the important lessons offered by eBay, Google, Verizon, IBM, Microsoft, Bank of America, drug companies, the Yellow Pages, and more